PENGARUH PEMAHAMAN WAJIB PAJAK TERHADAP KEPATUHAN PAJAK PENGHASILAN PASAL 23 PADA JASA TERMINAL PETIKEMAS SORONG - Fanny Jitmau; Pitter Leiwakabessy (Jurnal Pitis AKP, 2024)
Income Tax Article 23 is a provision in article 23 of the Income Tax Law regulating tax withholding on income received or obtained by domestic taxpayers and Permanent Enterprises derived from capital, service delivery, or organizers of activities other than those that have been deducted Income Tax Article 21, paid, provided for payment, or due by a government agency, a domestic corporate tax subject, an organizer of activities, a permanent business entity, or a representative of other foreign companies. The purpose of this study is to find out how the influence of taxpayers' understanding on Income Tax Article 23 compliance to all Sorong Container Terminal service users. Data collection techniques were obtained from the results of documentation, literature studies, and questionnaires. The type of research used is quantitative research using primary data. The results of this study show that Taxpayer Understanding has a very significant influence on the level of Income Tax Compliance 23 on Sorong Container Terminal Service Users